Support tools for building thermal rehabilitation - Novais, Ana (2012)
Countries development led to an increase use of energy resources that are essential to social and economic welfare of populations but damage the environment. This raise in energy use originated the increase of greenhouse gases emissions and the consequent climatic changes we all assist. Since only recently sustainability and energy efficiency issues have gained special relevance, especially in the Portuguese context, there is a great potential for the development of methodologies and strategies to improve the energy efficiency of buildings and to diagnose and repair thermal pathologies. The Mediterranean area, in which Portugal is included, is a privileged area when compared with other parts of Europe because of its mild climate. However, buildings show very high heating needs and unnecessary cooling needs but also high improvement potential. It is possible to drastically reduce the heating needs by acting on the envelop and promoting efficient HVAC systems and reducing or even eliminating cooling needs as well as DHW needs by promoting efficient shading, thermal mass and the use of solar collectors. This work intends to characterize the thermal performance of Portuguese residential buildings identifying their main thermal pathologies resulting from a bad design of the envelope and proposing the most appropriate improvement measures to reduce or even eliminate these pathologies. To achieve these goals, a thermal diagnostics software tool is being developed taking into account the analysis of the envelope, the HVAC systems and existing pathologies. This tool will help designers to define their rehabilitation strategies towards improved buildings energy performance in a cost/benefit perspective.